Alveolar nitric oxide in adults with asthma: evidence of distal lung inflammation in refractory asthma. - Berry, M; Hargadon, B; Morgan, A; Shelley, M; Richter, J; Shaw, D; Green, R; Brightling, C; Wardlaw, A; Pavord, I (2005)
Recent studies have suggested that alveolar nitric oxide (NO) concentration is a noninvasive test of distal lung inflammation. The current study determined whether alveolar NO concentration can be measured in patients with asthma of varying severity, tested the hypothesis that there is an association between alveolar NO and bronchoalveolar lavage (BAL) eosinophil count and determined whether refractory asthma is characterised by a raised alveolar NO concentration. Finally, the present authors assessed the effect of 2 weeks of prednisolone (30 mg q.d.) on alveolar NO concentration. Alveolar NO concentration was both measurable and repeatable in patients with refractory asthma. A positive correlation was found between alveolar NO concentration and BAL eosinophil count but not with bronchial wash or sputum eosinophil count. Alveolar NO concentration was increased in patients with refractory asthma (7.1 ppb) compared with mild-to-moderate asthma (3.4 ppb) and normal controls (3.4 ppb) and reduced by treatment with prednisolone. In conclusion, these findings support the hypothesis that alveolar nitric oxide is a measure of distal airway inflammation and suggest that distal lung inflammation is present in refractory asthma.